Perceived child-rearing practices as predictors of relationship satisfaction of fourth-year university hostel residents - Lowe, Charrisse (University of the Free State, 2005)
The focus of this research was to determine the effects that perceived child-rearing practices (as defined by sex education, perceived parenting styles and family structure) have on the relationship satisfaction of fourth-year hostel residents of the University of the Free State. The literature suggests child-rearing practices play an important role in later relationship satisfaction. Despite its importance, this is a concept that has not been explored in depth. Consequently, the South African research that is available on this topic is limited. All the hostels housing fourth-year residents on the University of the Free State’s Bloemfontein campus were involved in this study. The sample consisted of 364 fourth-year students. Questionnaires were sent to all the residents, 170 of which were returned. The data were analysed by means of a hierarchical regression analysis. The results indicated that sex education has an effect on relationship satisfaction, specifically on the liberated beliefs of sexual roles. Similarly, it was found that perceived parenting styles have an effect on the relationship satisfaction of students, but in this case on assertive conflict resolution/communication, independence, and intimacy. Although encouraging, the results of this study should be considered in light of the limitations of the study.

Die fokus van die navorsing was om die moontlike gevolge van waargenome kinderopvoedingspraktyke (in terme van seksopvoeding, waargenome ouerskapstyle en gesinsstruktuur) op die verhoudingstevredenheid van vierdejaar-koshuisinwoners van die Universiteit van die Vrystaat te bepaal. Bestaande literatuur in hierdie verband suggereer dat die kinderopvoedingspraktyke ‘n belangrike rol speel in hulle latere verhoudingstevredenheid as volwassenes. Ten spyte van die belangrikheid van hierdie aangeleentheid, is die geldigheid van die siening nog nie in diepte ondersoek nie. Gevolglik is die beskikbare Suid-Afrikaanse literatuur oor hierdie onderwerp beperk. Al die koshuise op die Universiteit van die Vrystaat se Bloemfontein kampus, waarin vierdejaarstudente woonagtig is, is by die onderhewige ondersoek betrek. Vraelyste is aan die geïdentifiseerde steekproefgroep van 364 vierdejaarstudente gestuur, waarvan 170 terugontvang is. Die data is met behulp van hiërargiese regressie-ontledings geanaliseer. Die resultate dui daarop dat seksopvoeding wel ‘n effek op latere verhoudingstevredenheid het, spesifiek soos dit tot uitdrukking kom in meer verligte houdings ten opsigte van geslagsrolle. Eweneens dui bevindinge daarop dat waargenome ouerskapstyle ’n invloed op die verhoudingstevredenheid van studente het. In hierdie geval spesifiek op assertiewe konflikoplossing/kommunikasie, onafhanklikheid, en intimiteit binne verhoudings. Alhoewel die resultate bestaande aannames bevestig, moet dit egter na waarde geskat word teen die agtergrond van die beperkings van die onderhewige ondersoek.
Dissertation (M.A. (Counselling Psychology))--University of the Free State, 2005
Keywords: Child rearing; Interpersonal relations; Intimacy (Psychology); Parent and child; Sex instruction for children; Relationship satisfaction; Parenting styles; Fourth-year students; Intimacy; Over-protection; Independence; Sex education; Family structure